Penerapan Sistem Artifical Intelligence Pada Alat Keamanan Gerbang Otomatis Wilayah Perumahan - Fuadi Hasani, Rifqi; Muhammad Yusuf (Politeknik Negeri Jakarta, 2024)
People are worried about the increasing crime such as theft in housing, so a reliable security system, including automatic gates with IoT (Internet of Things) and AI (Artificial Intelligence) is needed. AI can detect faces to improve security and facilitate access, keeping the environment safe. The use of IoT and AI enables a smarter and more responsive security system, reducing the risk of crime and increasing comfort. This system uses Python, Webcam, and Raspberry Pi to improve security and access efficiency. Python programs object detection and facial recognition algorithms, while the Webcam captures images or videos. Raspberry Pi as the processing center runs an AI model that recognizes vehicles and occupant identities based on facial features, ensuring that only registered occupants can open access, thereby improving security and housing access control. Test results show that the detection system works quite well in identifying vehicles and faces, with an average combined accuracy of 66.5%, which is obtained from the results of testing the object detection system (58%) and facial recognition (75%). QoS measurements of the Telkomsel LTE module show very good performance with a Throughput of 380.58 bps, Packet Loss 0%, and Delay 3.4 ms. The average download value of 19 Mbps, upload 4 Mbps, and ping 32 ms is also adequate.